Socio-economic factors influencing peoples’ participation in forest management in Benue-Plateau region, Nigeria (2009)
Socio-economic variables of respondents from Benue-Plateau region of North-Central Nigeria were studied to determine their possible influence on participation in Forest Management. Multistage random sampling technique was employed for the selection of 460 respondents living in and around communal forest areas for questionnaire interview and 240 participants for focus group discussion. In addition, in-depth interviews were held with Directors of Forestry in each State. Data generated were analyzed at p = 0.05 using Logistic Regression to determine factors that influence participation in forest management in the study area. It was found that age (p = 0.018) and occupation (p = 0.000) had significant influence on aggregate participation. Also, occupation was found to have influence on individual participation in physical execution of work (P = 0.010), issuance of advice or directive (P = 0.000), decision making, (P = 0.000), donation of land (P = 0.000), leadership role (P = 0.000) as well as monitoring, directing and evaluation (P = 0.000). Age was found to have influence on donation of land (P=0.046) while attainment of primary education (P=0.018) and secondary education (P=0.000) were found to have influence on donation of land.